ZaligVinder: A generic test framework for string solvers. Issue 4 (28th October 2021) - Kulczynski, Mitja; Manea, Florin; Nowotka, Dirk; Poulsen, Danny Bøgsted
Abstract: The increased interest in string solving in the recent years has made it very hard to identify the right tool to address a particular user's purpose. Firstly, there is a multitude of string solvers, each addressing essentially some subset of the general problem. Generally, the addressed fragments are relevant and well motivated, but the lack of comparisons between the existing tools on an equal set of benchmarks cannot go unnoticed, especially as a common framework to compare solvers seems to be missing. In this paper, we gather a set of relevant benchmarks and introduce our new benchmarking framework to address this purpose. Abstract : The increased interest in string solving in the recent years has made it very hard to identify the right tool to address a particular user's purpose. Generally, it lacks of comparisons between the existing tools on an equal set of benchmarks, especially as a common framework to compare solvers seems to be missing. In this paper, we gather a set of relevant benchmarks and introduce our new benchmarking framework to address this purpose.